Representaciones Sociales Sobre Enseñanza Y Aprendizaje Que Sostienen Docentes De Nivel Medio Superior Y Superior - Hernández, Juan Alberto Acosta; Vázquez, Miriam Martínez; Anaya, Arturo Curiel; Rodríguez, Aarón Reyes; Tarasenko, Anna; Guerrero, Carlos Rondero (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the social representations (SR) on mathematics, teaching and learning that have upper and middle level teachers who participated in a workshop on the use of a MOOC (Massive Open Online Course). It is used as an element of support for a Pre-Calculus face-to-face course. Using a questionnaire, the SR on the teaching and learning of mathematics were identified, as well as specific SR about the concept of inequality and the use of technology in the classroom. Based on the responses of the questionnaire, dimensions were captured that focuses on a particular meaning. This, therefore, is with the intention of organizing categories that would allow the establishment of hierarchies of the contents immersed in the field of SR of teachers.